Water filtration through a grainy layer with decreasing rate - Grabovskyi P. А. (Reports of the National Academy of Sciences of Ukraine, 2016)
A mathematical model of the rapid filter working with decreasing speed is got, and the algorithm of numeral realization of the model by PC is developed. The computations show the complete accordance of the results to the physical ideas of the process.